2017
DOI: 10.1177/0306624x17698054
|View full text |Cite
|
Sign up to set email alerts
|

The “Watchful Eye of God”: The Role of Religion in the Rehabilitation and Reentry of Repentant Jewish Prisoners

Abstract: Can participation in a religious rehabilitation program benefit a released prisoner's reentry into the community, and if so, how? Which elements of the religious worldview can be translated into tools for promoting desistance? Using a qualitative approach, we conducted 30 interviews with released prisoners from 3 months to 5 years beyond release who participated in a Jewish faith-based rehabilitation program administered by Israel's Prisoner Rehabilitation Authority. We interviewed participants in the Torah Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Why do so many prisoners seek religious instruction and guidance while incarcerated? What aspects (or dimensions) of religiosity are translated into tools for promoting lawabiding behaviors and a life free of recidivism (Morag and Teman 2018)? For the longest of times, stories of prisoner restoration, redemption, and the quest for behavioral change have captured the research interests of various scholars across several disciplines.…”
mentioning
confidence: 99%
“…Why do so many prisoners seek religious instruction and guidance while incarcerated? What aspects (or dimensions) of religiosity are translated into tools for promoting lawabiding behaviors and a life free of recidivism (Morag and Teman 2018)? For the longest of times, stories of prisoner restoration, redemption, and the quest for behavioral change have captured the research interests of various scholars across several disciplines.…”
mentioning
confidence: 99%
“…They no longer had time, boredom, privileges, or desired segregation from other prisoners. Elsewhere (Morag & Teman, 2018), we discuss how the men used religious tools toward desistance, and how they believe religion safeguarded them from “falling”; here, we end with the suggestion that it was for the intrinsic benefits of religion that they had internalized in the religious wards that they chose to be released into the religious reentry program and to continue to be observant on the outside.…”
Section: Resultsmentioning
confidence: 99%
“…By exploring the path of these men, who went through these stages of religious invigoration and chose to continue to “strengthen” religiously on the outside, we can better understand the various stages of the invigoration process in prison and its benefits. Elsewhere (Morag & Teman, 2018), we have described the religious reentry program and the religious tools that men felt helped them negotiate their return to society. Here, our focus is on the stages of religiosity during incarceration.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, 30 inmates who participated in the Torah Study Program reported that they have gained a number of "spiritual" tools. Some of the tools that were mentioned are, "guidance from above and obligation to god", the perceptions of the good things that happen in the world as "miracles" and the more difficult things as "challenges" or "tests, the role of religion as a supervisory tool, the positive values that religion instills in its believers and the positive routine accomplished through religious rituals, symbols and practices (Morag and Teman, 2018).…”
Section: Qualitative Studies On Religious Programs In Prisonmentioning
confidence: 99%
“…Throughout the history of corrections, religion and its institutions played a key role in shaping punishment and rehabilitation of offenders (Clear, Hardyman, Stout, Lucken, and Dammer, 2000;Johnson, 2004;Morag and Teman, 2018;Ronel, 2015;Ronel and Ben-Yair, 2017;Schaefer, Sams, and Lux, 2016;Wilson, 2016;Yun and Lee, 2016). Within this perspective, offenders are viewed as morally flawed, and the pursuit of moral and spiritual correction of their souls through atonement, work, obedience, and prayer -are common practices in the rehabilitating of offenders (Dodson et al, 2011;Ronel and Ben-Yair, 2017;Schaefer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%